Jealousy in Mixed Families: A Psychosocial Analysis of Stepmothers' Violence Against Stepchildren in Pontianak - M Zainul Hafizi (International Journal of Applied Research and Sustainable Sciences, 2024)
This study analyzes jealousy within blended family structures and its impact on violence against stepchildren, focusing on a case in Pontianak. A qualitative case study approach was employed, using data from police reports and relevant podcast interviews. The findings reveal that the stepmother's jealousy, triggered by the husband's unequal attention between biological and stepchildren, led to emotional tension that escalated into physical violence. Social pressures and the inability to manage jealousy exacerbated conflicts within the family. The study highlights the importance of healthy emotional management and social support in preventing domestic violence, particularly within blended families.